The predisposition of Small Medium Enteprises (SMEs) in Malaysia in penetrating international markets: (Agro based sector) / Rosnilawati Rusdi - Rusdi, Rosnilawati (2009)
The study was done between December 2008 and April 2009 to identify the predisposition of SME in penetrating international market by focusing in the manufacturing agro based sector. Fifty small and medium enterprises comprising in Kelantan was selected for the study using the method of simple random sampling. The small businesses that were studied were in the manufacturing/production, trade and services sub-sectors but focusing more on foods and beverages products. The problem statement for this research is about to find the predisposition of SMEs to penetrate international markets. This study was mentioned with three objectives stated to examine the predisposition of SMEs in penetrating international markets, to study the most influence factors that will influence SMEs to penetrate international markets and to determine whether there is a relationship of predisposition by SMEs to export with Independent Variables. In addition, a correlation model was used to analyze the relationship between dependent variable and independent variable. The results of the correlation analyze showed that the entire five variable are significant with the dependent variable. This study also includes some recommendations emanating from the study to make SMEs more effective in future.